2016
DOI: 10.1080/03630269.2016.1201487
|View full text |Cite
|
Sign up to set email alerts
|

Hb E-β-Thalassemia in Five Indian States

Abstract: Hb E [β26(B8)Glu→Lys; HBB: c.79G > A]-β-thalassemia (β-thal) has an extremely variable clinical presentation. We report the clinical features of these patients from five Indian states together with their hematological and molecular characteristics. Seventy-eight Hb E-β-thal patients from different regions [West Bengal (30), Maharashtra (21), Uttar Pradesh (13), Bihar (11), Orissa (3)] were clinically evaluated along with hematological profiles and molecular characteristics (β-thal mutations, XmnI polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The most common thalassemia disease found in northeast Thailand is hemoglobin E - β - thalassemia ( Hb E - β - thal) 2. It has been shown that clinical severity of this disease is variable, ranging from mild to severe transfusion-dependent thalassemia 36. Patients with transfusion - dependent Hb E - β - thal disease require lifelong regular blood transfusion for survival, while NTDT patients generally have mild anemia and do not require regular blood transfusion for survival.…”
Section: Introductionmentioning
confidence: 99%
“…The most common thalassemia disease found in northeast Thailand is hemoglobin E - β - thalassemia ( Hb E - β - thal) 2. It has been shown that clinical severity of this disease is variable, ranging from mild to severe transfusion-dependent thalassemia 36. Patients with transfusion - dependent Hb E - β - thal disease require lifelong regular blood transfusion for survival, while NTDT patients generally have mild anemia and do not require regular blood transfusion for survival.…”
Section: Introductionmentioning
confidence: 99%
“…This results in a dilemma while offering genetic counselling to couples at-risk. Our recent study on HbE-b-thalassemia patients showed that 37.2% of patients had a mild phenotype [19] which was higher than that reported in Southeast Asia. Also, there are many severe patients who do not take regular blood transfusions due to various social and economic reasons and commonly present with severe ineffective erythropoiesis, peripheral hemolysis, iron overload and hypercoagulability leading to organ damage particularly in low and middle income countries including India [20].…”
Section: Discussionmentioning
confidence: 54%
“…Recent reports have shown that HbE-b-thalassemia is also seen in other states of the country in different ethnic groups both due to migration of people in search of a better livelihood and due to inter-marriages between communities which was not common earlier. Thus, certain population groups in West Bengal, Maharashtra, Uttar Pradesh, Bihar, Chhattisgarh, Jharkhand and Orissa have an overlapping distribution of both the b-thalassemia gene and the HbE gene [3,19,21] resulting in a high number of HbE-bthalassemia cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical manifestations varied widely from mild form of thalassemia intermedia to severe thalassemia major when β E -thalassemia co-inherited with other type of β-thalassemia [17]. Some severe patients would present with hepatosplenomegaly, severe anemia, skeletal disease and need receive intermittent or regular blood transfusions [18]. For this reason, HbA 2 parameter should be considered in case of β E /β N being ignored in the β-thalassemia screening in high risk couples.…”
Section: Discussionmentioning
confidence: 99%